Resultados da monitorização dos habitats de interesse comunitário em Portugal - Meireles, Catarina (2020)
The Habitats Directive establishes that Member States must apply the necessary measures to maintain and/or restore a favourable conservation status for habitat types & species of community interest. To monitoring this process, Article 17 requires Member States to report on a regular basis, to the European Commission and to all European citizens, on the progress of implementing this Directive. Therefore, every six years, all countries must produce a monitoring report assessing on species and habitats conservation status throughout their territory, both in and outside the Natura 2000 network. In Portugal, three national reports under Article 17 have been completed for the periods 2001-2006, 2007-2012 and 2013-2018. These reports include, for each biogeographic region, an assessment of the conservation status of each target value. For habitats, this goal was achieved analysing separately a set of specific parameters: Range, Area, Structure/Function and Future Perspectives. In this conference we will present the main results of the 2013-2018 assessment for habitats of Community interest - done in a partnership between ICNF and PHYTOS, with the collaboration of an important set of national experts. We will also present the main progresses achieved and the main differences between 2001 and 2018. These results highlight [1] the lack of data in habitat distribution outside the Natura 2000 Network; [2] the continuous degradation of several habitats, including coastal habitats, water-plane habitats and forest habitats; [3] as well as changes in threats pattern.